Pre-service teachers’ scientific explanation with e-scaffolding in blended learning - Amelia, Rizki; Rofiki, Imam; TORTOP, Hasan Said; ABAH, Joshua Abah (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2020)
This study aims to examine the effect of e-scaffolding in blended learning on pre-service teachers' scientific explanation abilities as well as to find out the patterns of scientific explanation of pre-service teachers who learn by e-scaffolding in blended learning. This study employed mixed-method with concurrent embedded design. Quasi-experimental research design in the form of a one-group pretest-posttest control group design was used as a quantitative approach, whereas the learning process and scientific explanation patterns were described in a qualitative approach. The population of this study was 152 elementary school pre-service teachers of a state university at Malang, while the sample was 24 elementary school pre-service teachers in the seventh semester. The sample selection technique in the study was purposive sampling. The instrument used for measuring scientific explanation abilities was problem descriptions. The quantitative data were analyzed using the t-test, while qualitative data were analyzed using descriptive method. The finding of the study indicated that pre-service teachers' scientific explanation improved after learning with e-scaffolding in blended learning. The pre-service teachers were able to explain the relationship between theory and problems very well. The recommendation for future research, it is crucial to investigate the characterization of scientific explanation